Intellectual Capital and Corporate Governance on The Profitability of Indonesian State-Owned Enterprises - Rachmawati, Rima (CENTRAL ASIA AND THE CAUCASUS, 2022)
The purpose of this research is to prove the decline in profitability of Indonesian- Owned Enterprises in the period due to lower disclosure of intellectual capital and governance in the annual reports of Indonesian Government-Owned Enterprises. The method of this research expected to provide convenience too Owned Enterprises. Data analysis uses multiple regressions with 51 populations with the results of the study stating a partial relationship that the disclosure of intellectual capital and corporate governance in the annual report can increase the profitability of state-owned companies.